2023
DOI: 10.23876/j.krcp.22.240
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 incidence and outcomes among patients with kidney replacement therapy

Siribha Changsirikulchai,
Pornpen Sangthawan,
Jirayut Janma
et al.

Abstract: Background: We aimed to investigate the incidence, fatality, and associated factors in patients with hemodialysis (HD), peritoneal dialysis (PD), and kidney transplantation (KT) hospitalized for coronavirus disease 2019 (COVID-19) infection and reimbursed from the National Health Security Office (NHSO). Methods: The retrospective cohort analysis was conducted from an electronic-claimed database, and COVID-19 vaccination status was evaluated in patients with HD, PD, and KT from January 2020 to December 2021. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This study did not find significant differences in the risk of death from COVID-19 between HD and PD patients. In Thailand, HD patients tended to have a higher mortality rate compared with PD patients, but the difference was not significant [14]. Although the PD group was likelier to stay at home and maintain social distancing, age and comorbidities may have impacted patient mortality more than the dialysis modality.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This study did not find significant differences in the risk of death from COVID-19 between HD and PD patients. In Thailand, HD patients tended to have a higher mortality rate compared with PD patients, but the difference was not significant [14]. Although the PD group was likelier to stay at home and maintain social distancing, age and comorbidities may have impacted patient mortality more than the dialysis modality.…”
Section: Discussionmentioning
confidence: 92%
“…A United States study of 28,503 randomly selected patients from approximately 1,300 dialysis facilities found a SARS-CoV-2 seroprevalence of 9.3%, with an estimated seropositivity of 9.2% in the adult population of the United States at the same time [13]. Meanwhile, a nationwide cohort study in Thailand reported that the overall incidence of COVID-19 infection in patients with kidney replacement therapy (HD, PD, and KT) was 4% which is similar to the rate of 3.4% for the general population [14]. In this study, the COVID-19 infection rates for HD and PD patients were 1.3% and 1.2%, respectively, similar to the 1.22% infection rate for the general population in Korea reported by the Korea Disease Control and Prevention Agency [15].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Over the past 4 years since the outbreak began, many studies have been conducted on COVID-19. However, Korean data comparing the incidence and outcomes of COVID-19 based on RRT modality in patients with kidney failure are lacking [8,9]. Here, we aimed to analyze COVID-19 incidence and COVID-19-related hospitalization and mortality rate based on RRT modality in patients with ESKD.…”
Section: Introductionmentioning
confidence: 99%